An Overview of Madrasah Model of Education in Indonesian System of Education: Opportunity and Challenges - Husin, Saifuddin Ahmad (Madrasah: Jurnal Pendidikan dan Pembelajaran Dasar, 2018)
Madrasahs evolved from Pesantren model of education. While pesantrens were the comparative model of the colonial Dutch model of education, madrasahs are hybrid model of the two. The emergence and development of madrasahs is based on Islamic principle of â€œkeeping traditions and adopting the new when it is better.â€ There is distinction between Madrasahs and Pesantren. Madrasahs are general education schools run by Islamic institutions to provide education to Muslim pupils together with religious instruction. Pesantren are Islamic Boarding Schools for teaching Islamic studies. Some madrasahs are part of the pesantren system, others are not. In decentralization perspective madrasahs face the challenges of ensuring district government to maintain a vibrant private madrasah community, addressing common fears that their Islamic characteristics will disappear, dividing the line between general and religious education when madrasah teach an Islamic approach to general education balancing the demands for improved quality and increased enrolment.